If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (37b + -5) + -9(4b + 1) = -3 Reorder the terms: (-5 + 37b) + -9(4b + 1) = -3 Remove parenthesis around (-5 + 37b) -5 + 37b + -9(4b + 1) = -3 Reorder the terms: -5 + 37b + -9(1 + 4b) = -3 -5 + 37b + (1 * -9 + 4b * -9) = -3 -5 + 37b + (-9 + -36b) = -3 Reorder the terms: -5 + -9 + 37b + -36b = -3 Combine like terms: -5 + -9 = -14 -14 + 37b + -36b = -3 Combine like terms: 37b + -36b = 1b -14 + 1b = -3 Solving -14 + 1b = -3 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 1b = -3 + 14 Combine like terms: -14 + 14 = 0 0 + 1b = -3 + 14 1b = -3 + 14 Combine like terms: -3 + 14 = 11 1b = 11 Divide each side by '1'. b = 11 Simplifying b = 11
| 5x-7=2x^2+3(3) | | 3.5x+6.5+7=-20.5 | | 18(x+2)=9x+5 | | (47+x)/3=11+x | | -6x^4y^3z-12x^5y^3-18x^4y^2z=0 | | -6x-8=3x+10 | | 5y+2(y-4)=5(y+1)-4 | | 5(2-x)+8=3(x-6) | | (5x-7)=(4x+11)(x) | | 48-x=4*a/7 | | cos*2*x+sin*x=0 | | 5/4x-9/x=2 | | 5(5x+8)=25x+40 | | 3f+2=-2f-8 | | x+(x+24)+(x+24)(2)=376 | | sin*2(x)*sin(x)=cos(x) | | -7-3x=11 | | 5(-8)+6(-8)+4+9=7(-8)+5+3(-8) | | 14x^3-68x^2-10=0 | | 2x^2+3=4x+11(0) | | 7x+6x+3+9=7x+5+5x | | 5x-7=4x+11(1) | | -6x^2-2x+3=0 | | 12+2m=m+13 | | 5x-7=4x+11(x) | | 2y+1=7x-3 | | 3x-3y-9x+7y=0 | | 5x-7=4x+11 | | 15+y-7.2=4.5 | | 3w^2+0w-75=0 | | -16t^2+20t+5=20t | | 7x-8-11x=0 |